Homeowner mitigation decision‐making: Exploring the theory of planned behaviour approach. Issue 4 (5th October 2020) - Slotter, Rachel; Trainor, Joseph; Davidson, Rachel; Kruse, Jamie; Nozick, Linda
Abstract: During hurricanes, flooding and wind cause property damage and loss of life. Increased coastal development and recent economic impacts of hurricanes has increased stakeholders' interest in coastal mitigation. Through the use of the Theory of Planned Behaviour, this study focuses on factors that impact the intention of homeowners to mitigate. Methodologically, surveys were sent to a random sample of 2, 500 coastal North Carolina homeowners who provided insights about their hurricane and mitigation experiences. The sample was purchased from Genesys, which utilises the postal service's database to randomly select addresses. Binary logistic regression was used to compute homeowners' intention to adopt eight separate mitigation actions for their homes. The findings show limited support on the influence of emotion and risk perception on intention to mitigate. However, the findings clearly support the relationships between intention to mitigate and the influence of others and perceptions of the characteristics of the mitigation actions. The significance of the findings indicates the importance of utilising these factors in future studies to better understand mitigation decision‐making and to inform future mitigation policies and programs.